PENGARUH KEPEMILIKAN MANAJERIAL, INSTITUSIONAL, ARUS KAS BEBAS DAN ASET YANG DIJAMINKAN TERHADAP KEBIJAKAN DEVIDEN PADA PERUSAHAAN MANUFAKTUR YANG LISTING DI BEI - Solekah, Nihayatu Aslamatis (IQTISHODUNA, 2013)
" The purposeof this research is to examine Managerial Ownership (MOWN), Institutional Ownership(INST), Free Cash Flow (FCF) and Collateralizable Asset (COLLAS) have an effect on either throughsimultaneous and also partial to Devidend Payout Ratio (DPR) at manufacturing industry that go public inJakarta Stock Exchange of during 2000–2005. It is repetition and adaptation of the Rozeff research (1982) andMollah research (2000). This research is inclusive the type of explanatory research. Connecting sample wasconducted with the approach of non probability sampling with the technique of purposive sampling speciallythe type of judgement sampling. Analysis methode used by multiple regression analysis.The result of thisresearch indicates the variable of Managerial Ownership (MOWN), Institusional Ownership (INST), FreeCash Flow (FCF) and Collateralizable Asset (COLLAS) by simultaneous have the influence which significantto Devidend Payout Ratio (DPR). It is suggested that whoever conducts a further study expand the scope ofanalysis aspect, as the researcher is aware that the aspects other than those used in this study, there are othervariables need examined influencing the devidend payout ratio.